A HYBRID OF TRADITIONAL TELEPHONE SERVICE AND COMPUTER BASED INTERNET TELEPHONY - Alemseged, Yohannes; Devarajan, G. (Zede Journal of Ethiopian Engineers and Architects, 2023)
A Hybrid of Traditional Telephony and Internet Telephony is a communications network that integrates the traditional Public Switched Telephone, Network (PSTN) and the Internet Protocol (IP) based packet switched network. In this work various types of hybrid PSTN-IP telephony connections including the currently available service are explored. Selected hardware and software tools have been used to develop a hybrid Internet telephony service in LAN The Microsoft product TAPI 3.0 is used to develop all the interfaces and the ITU-T H.323 standard is used as the voice over IP. The software developed for this work has been tested and found working satisfactorily. The problem associated with full duplex on line communication is also addressed. This system has been implemented successfully.